Sinonasal mixed transitional epithelial-seromucinous papillary glandular neoplasms with BRAF p.V600E mutations — sinonasal analogues to the sialadenoma papilliferum family tumors - Patel, Simmi; Snyderman, Carl H.; Müller, Sarina Katrin; Agaimy, Abbas; Seethala, Raja R. (Virchows Archiv, 2022)
Sinonasal non-intestinal type adenocarcinoma (non-ITAC) is a heterogeneous category that may benefit from improved taxonomy. With the recognition that most non-ITAC are phenotypically seromucinous, stratification may be improved by applying salivary type morphologic criteria and molecular findings. We report two cases of papillary seromucinous adenocarcinoma with sinonasal papilloma-like surface components that show histologic and molecular features analogous to the salivary sialadenoma papilliferum family of tumors. Case 1 concerns a 50-year-old female who presented with a left anterior nasoethmoid polyp, while case 2 is that of a 74 year old female with nasal polyposis. Histologically, both cases demonstrated a surface transitional sinonasal papilloma-like component (more prominent in case 2) with a deeper bilayered glandular component showing papillary and tufted micropapillary growth of monomorphic columnar to cuboidal cells with eosinophilic cytoplasm. Case 1 also showed a deep cribriform/microcystic component. Immunostains showed a delimiting p63/p40 positive basal layer around the SOX-10 positive glandular elements, while the transitional sinonasal papilloma-like components were diffusely p63/p40 positive. Like sialadenoma papilliferum and related tumors, both cases demonstrated BRAF p.V600E mutations in both components and no other alterations. The patients remain disease free at 9 and 19 months respectively. Our cases illustrate a novel sinonasal lesion and suggest that improved morphologic and molecular categorization may refine and reduce the category of non-ITAC.
CRIS-Team Scopus Importer:2022-07-01
Keywords: BRAF p.V600E; Non-intestinal type sinonasal adenocarcinoma; Non-salivary type sinonasal adenocarcinoma; Salivary type-adenocarcinoma; Sinonasal papilloma